2010
DOI: 10.1073/pnas.0914613107
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning sculpts the dendritic arbor of adult-born hippocampal neurons

Abstract: Neurogenesis in the hippocampus is characterized by the birth of thousand of cells that generate neurons throughout life. The fate of these adult newborn neurons depends on life experiences. In particular, spatial learning promotes the survival and death of new neurons. Whether learning influences the development of the dendritic tree of the surviving neurons (a key parameter for synaptic integration and signal processing) is unknown. Here we show that learning accelerates the maturation of their dendritic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 51 publications
9
189
0
2
Order By: Relevance
“…Blockade of N-methyl-D-aspartate (NMDA) receptors does not disrupt learning-induced changes in cell numbers (Tronel et al 2010). These results are consistent with the role of NMDA during the developmental period (Rajan and Cline 1998;Sin et al 2002;Niell et al 2004;Prithviraj and Inglis 2008).…”
Section: Mechanismssupporting
confidence: 76%
See 3 more Smart Citations
“…Blockade of N-methyl-D-aspartate (NMDA) receptors does not disrupt learning-induced changes in cell numbers (Tronel et al 2010). These results are consistent with the role of NMDA during the developmental period (Rajan and Cline 1998;Sin et al 2002;Niell et al 2004;Prithviraj and Inglis 2008).…”
Section: Mechanismssupporting
confidence: 76%
“…Interestingly, there is no critical time window for experience-induced dendritic plasticity of adult-born neurons as spatial learning sculpts the dendritic arbor of adult-born neurons even when they are several months old (Lemaire et al 2012). The effects of learning are specific for neurons born during adulthood as neurons born during development remained unchanged after learning (Tronel et al 2010;Lemaire et al 2012). …”
Section: Neurogenesis and Hippocampal Memory Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that these unique characteristics may make new neurons within this critical period more sensitive to life experience. In particular, it has been shown that learning or experiencing an enriched environment determines the survival, dendritic development, and population response of the new neurons (22)(23)(24)(25)(26). This exceptional plasticity of the young neurons may be particularly useful for information processing (27,28).…”
Section: Discussionmentioning
confidence: 99%